2000
DOI: 10.1021/np990614l
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the rol C Gene on Hairy Root:  Induction Development and Tropane Alkaloid Production by Atropa belladonna

Abstract: Two series of Atropa belladonna hairy root lines were obtained, the first one transformed via Agrobacterium tumefaciens harboring rol C and npt II genes, and the other transformed with rol ABC and npt II genes. Thirteen hairy root lines were obtained and selected on hormone-free medium. The transformation was confirmed by PCR analysis, and these root lines were first examinated for their growth rate. Then hyoscyamine and scopolamine production was measured after 3 and 4 weeks of culture to evaluate the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 20 publications
0
41
1
3
Order By: Relevance
“…The rol ABC genes were sufficient to sustain strong growth and high alkaloid production (8 mg·g -1 D.W.), with scopolamine concentrations rising to 2.5-fold those of hyoscyamine [31]. The rol C gene alone played a significant role in the hairy root growth rate (17-fold increase) [32]; however, this effect was much lower than that induced by the rol ABC genes together (75-fold increase). In contrast, the rol C gene alone was as sufficient as the rol ABC genes together (12-fold times more than in untransformed roots) to stimulate the biosynthesis of tropane alkaloids in Atropa belladonna hairy root cultures (Table 8.2).…”
Section: Hairy Roots and Tropane And Morphinan Alkaloid Accumulationmentioning
confidence: 95%
See 1 more Smart Citation
“…The rol ABC genes were sufficient to sustain strong growth and high alkaloid production (8 mg·g -1 D.W.), with scopolamine concentrations rising to 2.5-fold those of hyoscyamine [31]. The rol C gene alone played a significant role in the hairy root growth rate (17-fold increase) [32]; however, this effect was much lower than that induced by the rol ABC genes together (75-fold increase). In contrast, the rol C gene alone was as sufficient as the rol ABC genes together (12-fold times more than in untransformed roots) to stimulate the biosynthesis of tropane alkaloids in Atropa belladonna hairy root cultures (Table 8.2).…”
Section: Hairy Roots and Tropane And Morphinan Alkaloid Accumulationmentioning
confidence: 95%
“…In particular, rol ABC genes induce a higher rhizogenesis and could act indirectly on cell growth and on alkaloid production [31][32][33]. The growth of Agrobacterium-rhizogenes-transformed root cultures was independent of exogenous phytoregulators addition.…”
Section: Hairy Roots and Tropane And Morphinan Alkaloid Accumulationmentioning
confidence: 99%
“…It was known that fungal elicitors and other microbeassociated molecular patterns trigger a rapid ROS accumulation (oxidative burst), with subsequent activation of various defense systems [59]. As rolC expression led to activation of secondary metabolites [4,5,6,49,54] and pathogenesis-related proteins [37], the activation of ROS production by the oncogene could be expected. In contrast, earlier pharmacological studies suggested that ROS are not involved in the activator function of rolC [7].…”
Section: Ros Homeostasis and Expression Of Antioxidant Genesmentioning
confidence: 99%
“…Hairy root cultures of Atropa belladonna have been evaluated widely from different angles in terms of tropane alkaloid synthesis (Hashimoto et al, 1993;Aoki et al, 1997;Bonhomme et al, 2000;Dimitrov et al, 2005;Kursinszki et al, 2005). The tropane alkaloid production potentials of the hairy root cultures of another species of this genus, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Modern biotechnological techniques have been employed most extensively involving Atropa belladonna as a model system (Banerjee et al, 2002;Bonhomme et al, 2000). A. baetica, another species of this genus, has also gained ample attention in terms of biotechnological intervention (Zarate et al, 1997a,b;Zarate, 1999;Amongst the different biotechnological tools implemented so far concerning both A. baetica and more particularly A. belladonna, Agrobacterium rhizogenesmediated 'hairy root' cultures have attracted major research attention the world over in the area of in vitro production of plant-derived secondary products (Guillon et al, 2006;Milen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%